Energy storage devices for electronic systems : rechargeable batteries and supercapacitors - Kularatna, Nihal (Academic Press., 2015)
This book provides the opportunity to expand your knowledge of innovative supercapacitor applications, comparing them to other commonly used energy storage devices. It will strengthen your understanding of energy storage from a practical, applications-based point-of-view, without requiring detailed examination of underlying electrochemical equations. It provides explanations of the latest energy storage devices in a practical applications-based context; includes examples of circuit designs that optimize the use of supercapacitors, and pathways to improve existing designs by effectively managing energy storage devices crucial to both low and high power applications; covers batteries, BMS (battery management systems) and cutting-edge advances in supercapacitors, providing a unique compare and contrast examination demonstrating applications where each technology can offer unique benefits. --